A Randomized Trial of the Efficacy of Hand Disinfection for Prevention of Rhinovirus Infection - Turner, Ronald B.; Fuls, Janice L.; Rodgers, Nancy D.; Goldfarb, Heidi B.; Lockhart, Leslie K.; Aust, Louise B. (Clinical infectious diseases, 2012)
Background. Hand disinfection is frequently recommended for prevention of rhinovirus (RV) infection and RV-associated common colds. The effectiveness of this intervention has not been established in a natural setting. The purpose of this study was to determine the effect of hand disinfection on RV infection and RV-associated common cold illness in a natural setting. Methods. A controlled clinical trial was done in young adult volunteers during 9 weeks of the fall 2009 RV season. Volunteers were randomized to either an antiviral hand treatment containing 2% citric acid and 2% malic acid in 62% ethanol (n = 116) or to a no-treatment control group (n = 96). The hand treatment was applied every 3 hours while the subjects were awake. All volunteers kept a daily diary of symptoms and had a nasal lavage for polymerase chain reaction once each week and 2 additional lavages around the time of each common cold illness. The primary endpoint was the number of RV-associated illnesses. The incidence of RV infection and of common cold illnesses were evaluated as secondary endpoints. Results. The hand treatment did not significantly reduce RV infection or RV-related common cold illnesses. The total number of common cold illnesses was significantly reduced in the intent-to-treat analysis, but this effect was not seen in the per protocol analysis. Conclusions. In this study, hand disinfection did not reduce RV infection or RV-related common cold illnesses. Clinical Trials Registration. NCT00993759.